Noncommutative rings with elementary dividers - Zabavsky, В. V. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Maximally nonprincipal ideals of rings of finitely generated principal ideals are investigated. A new class of rings of elementary divisors is described.